Staff rotation: resources of the institutional channel of personnel professionalization and the instrument (procedure) of public service personnel management - Kuybida, Vasyl; Shpektorenko, Ihor (Public Administration and Regional Development, 2023)
In the article, the authors define the main tasks that should be solved by job rotation in the public (civil) service. Also, the authors proposed a system of functions as results of the personnel management process, which should be possessed by job rotation. The research was carried out in the paradigm of formation of professional mobility of personnel. The authors summarized that the following job rotation tasks are most common in practice: formation of professional competence, enrichment of professionalism, professional suitability; acquisition of competencies of related positions; transfer of personnel to other positions in order to determine the most optimal option for their placement; prevention of professional deformation; formation of personnel reserve; prevention of corruption. It is noted that suitability for job rotation also depends on the effectiveness of the previous professionalization process in terms of assessing the general professional mobility of the candidate as his ability to relatively quickly acquire relevant job competencies and switch to individual innovation in work. From a functional point of view, job rotation should be used in the processes of: professional orientation of personnel; its selection (recruitment, selection, selection) and subsequent professional evaluation; professional motivation; professional adaptation; for professional activation; continuous education (training) and professional education. It was concluded that the new vision of the functional purpose of job rotation consists in the fact that it can be productively used in the processes of: professional orientation of personnel; its selection (recruitment, selection, selection) and professional evaluation; professional motivation; professional adaptation; professional activation; continuous education (training) and professional education.